Exosomes from Ureaplasma parvum-infected ectocervical epithelial cells promote feto-maternal interface inflammation but are insufficient to cause preterm delivery - Tantengco, Ourlad Alzeus G.; Richardson, Lauren S.; Radnaa, Enkhtuya; Kammala, Ananth Kumar; Kim, Sungjin; Medina, Paul Mark B.; Han, Arum; Menon, Ramkumar (Frontiers in Cell and Developmental Biology, 2022)
This study determined if exosomes from ectocervical epithelial (ECTO) cells infected with Ureaplasma parvum (U. parvum) can carry bacterial antigens and cause inflammation at the feto-maternal interface using two organ-on-chip devices, one representing the vagina-cervix-decidua and another one mimicking the feto-maternal interface, and whether such inflammation can lead to preterm birth (PTB). Exosomes from U. parvum-infected ECTO cells were characterized using cryo-electron microscopy, nanoparticle tracking analysis, Western blot, and Exoview analysis. The antigenicity of the exosomes from U. parvum-infected ECTO cells was also tested using THP-1 cells and our newly developed vagina-cervix-decidua organ-on-a-chip (VCD-OOC) having six microchannel-interconnected cell culture chambers containing cells from the vagina, ectocervical, endocervical, transformation zone epithelia, cervical stroma, and decidua. The VCD-OOC was linked to the maternal side of our previously developed feto-maternal interface organ-on-a-chip (FMi-OOC). Cell culture media were collected after 48 h to determine the cytokine levels from each cell line via ELISA. For physiological validation of our in vitro data, high-dose exosomes from U. parvum-infected ECTO cells were delivered to the vagina of pregnant CD-1 mice on E15. Mice were monitored for preterm birth (PTB,